2009
DOI: 10.1002/pon.1536
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and psychosocial stress: quality of life over 2 years following breast cancer diagnosis and psychological impact factors

Abstract: Objective: The aim of this study was to investigate changes in the quality of life (QoL) and body image among breast cancer patients over 2 years and to examine different predictive factors for QoL 2 years after the primary operation.Methods: A total of 203 women with a primary diagnosis of breast cancer completed the questionnaires 2 weeks and 6, 12, 18, and 24 months after surgery. Quality of Life Questionnaire (QLQ-C30), Breast Cancer Specific Quality of Life Questionnaire Module (QLQ-BR23), Questionnaire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
93
4
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 41 publications
(92 reference statements)
15
93
4
13
Order By: Relevance
“…24 Other factors that increase risk of depression include a past history of psychiatric illness, 25 neurotic personality traits, 26 and ethnic/emigrant status. 27 Another factor related to depression in women with breast cancer is lack of a confiding relationship, and the most confiding relationship in this regard is often the spouse.…”
Section: Introductionmentioning
confidence: 99%
“…24 Other factors that increase risk of depression include a past history of psychiatric illness, 25 neurotic personality traits, 26 and ethnic/emigrant status. 27 Another factor related to depression in women with breast cancer is lack of a confiding relationship, and the most confiding relationship in this regard is often the spouse.…”
Section: Introductionmentioning
confidence: 99%
“…For the World Health Organization, the term QoL is defined as an individual's perception of his or her life position, in the context of culture, value system in which they live, regarding their goals, expectations, standards and concerns 2 . So, it is understood that several specific factors may change the QoL of a cancer patient, in addition to the tumor itself, such as the patient's ability to cope with the illness and the presence or absence of a supportive environment during the period 3,4 . Based on this background, and on the many factors that can cover QoL, it is believed that the QoL of patients with breast cancer can benefit from pet ownership, as well as those benefits are reported in several populations [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…While the methods used in the treatment of breast cancer extend the lifetime of the patient, they may also cause problems such as anxiety, depression, distortion of body image, infection, nausea, vomiting, and skin burns (2)(3)(4)(5). Among all symptoms, anxiety and depression are most often reported by cancer patients (6,7). In the studies conducted, it was stated that 30 to 50% of the women experienced anxiety and depression within the first year following mastectomy (4,5,8,9).…”
mentioning
confidence: 99%
“…In the case of a long-lasting treatment, the intense experience of uncertainty leads to despair causing depression (10). It was also demonstrated that anxiety and depression had an adverse impact on the quality of life (6,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation